2017
DOI: 10.1055/s-0043-104429
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy with Fovea-Sparing Internal Limiting Membrane Peeling for Myopic Foveoschisis

Abstract: Myopic foveoschisis is a rare form of a tractional maculopathy, which occurs in patients with elevated axial length. The contraction of the posterior hyaloid exerts tangential traction on the retinal surface with a subsequent continuous splitting of the retinal layers. Internal limiting membrane (ILM) peeling has been advocated in foveoschisis, but it has been associated with post-operative macular hole formation. We report on a modified surgical technique, which spares the fovea and may reduce the risk for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This patient had been diagnosed with epiretinal membrane, but he did not undergo ILM peeling during PPV. Many studies have reported the usefulness of ILM peeling [15,24]. It has also been reported that fovea-sparing ILM peeling can be an effective approach for treating MF without risk of MH [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient had been diagnosed with epiretinal membrane, but he did not undergo ILM peeling during PPV. Many studies have reported the usefulness of ILM peeling [15,24]. It has also been reported that fovea-sparing ILM peeling can be an effective approach for treating MF without risk of MH [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the usefulness of ILM peeling [15,24]. It has also been reported that fovea-sparing ILM peeling can be an effective approach for treating MF without risk of MH [24]. Huang et al [25] found that the prevalence of secondary MH RD after PPV without ILM peeling is high in patients with preoperative FD.…”
Section: Discussionmentioning
confidence: 99%
“… 35 As a result of this procedure, traction forces change their direction from centrifugal to centripetal, and the integrity of the end feet of the foveal Müller cells and macular structure is preserved. 13 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…2020). Additionally, many have proven that the rate of occurrence for secondary MH significantly decreased after PPV combined with fovea‐sparing ILM peeling (Seppey & Wolfensberger 2017). However, the traction caused by vascular stiffness and posterior staphyloma can only be resolved by MB in MFS eyes, particularly in cases of a thin foveal roof, outer lamellar holes and severe foveal detachment on OCT (Alkabes & Mateo 2018).…”
Section: Discussionmentioning
confidence: 99%